Predicting the mental health quality of adolescents with intensive exposure to metaverse and its counseling recommendations in a multicultural context - Muslihati Muslihati; Yuliati none Hotifah; Wahyu Nur Hidayat; Anabelie V Valdez; Edi Purwanta; Achmad Miftachul 'Ilmi; Nur Mega Aris Saputra (Jurnal Cakrawala Pendidikan, 2023)
Metaverse—an incredible medium that combines features of virtual reality platforms such as online games, social media, and the Internet—is predicted to bring significant changes to human behavior. It is believed that social interaction and the quality of mental health can be at risk once Metaverse becomes more prevalent with adolescents predicted to be the most vulnerable group. This study intends to prove this prediction by examining the effect of online game addiction and social media addiction on the mental health quality of adolescents as the majority group with Metaverse access. This correlational study involved 700 students from 14 schools in the greater Malang area. Data were collected through the Metaverse Impact Instrument (MII) and analyzed partially using the T-test and simultaneously using the F-test to know the contribution of gender using an independent sample T-test. Previously, the assumptions of multicollinearity and heteroscedasticity assumption were also tested. The results indicate that online games and social media negatively affect mental health at a rate of 31.5%. These results provide empirical evidence for theoretical predictions regarding the impact of Metaverse on mental health quality in adolescents. As a follow-up, research is needed to develop educational intervention strategies, appropriate guidance, and counseling services that purpose is to: 1) integrate cultural and religious values into character education; 2) anticipate the potential risks of metaverse among adolescents.